Bases conceituais da teoria histórico-cultural : implicações nas práticas pedagógicas - Garay González, Abel Gustavo (Universidade Federal de São Carlos, 2012)
The intention of this research was to analyze and clarify the conceptual foundations of the Historical-Cultural Theory, based on the Historical-Dialectical Materialism by Marx, and their direct implications for the pedagogical practices, specifically on the processes of teaching and learning, in order to contribute to the Brazilian Basic Education, in the search to understand and overcome the problems related to the difficulties of teaching and student learning. The Historical-Cultural Theory is based on the Historical-Dialectical Materialism by Marx and has its methodological foundation founded in the microgenetic analysis. The Marxist theoretical presumptions assists Vigotsky s analysis with the discussion of humans being not only a biological structure, but rather a consequence of the historical-cultural relation, having work as the main mediator. Vigotsky and collaborators present important theoretical and practical contributions to the understanding of the dialectical relations between Teaching and Learning. Vigotsky s microgenetic analysis shows us how to overcome this dilemma between the processes of teaching and learning. From Vigotsky s point of view, the pedagogical processes are intentional, deliberate, and the school is the place where the intentional pedagogical intervention triggers the learning and quality teaching processes. The research is of a bibliographic nature and uses two sources: the primary ones, pieces of work of authors from the Historical-Cultural Theory, and the secondary ones, pieces of work of authors who interpret the primary pieces of work. The question that guided the research was: What are the core concepts of the Historical-Cultural Theory, based on the Marxist theory and its implications for the pedagogical practices? The objectives outlined to answer this theme were: to analyze, in the writings of the Marxist philosophy, the major theoretical points of the Historical-Dialectical Materialism that assist the Historical-Cultural Theory; to clarify the contributions to the Historical- Cultural Theory to the understanding of the dialectical relations in the processes developed in the pedagogical practices. The results clearly show the necessity of overcoming the biological paradigm of Education and presenting an educative model oriented around the viewpoint of society, of human being and of knowledge as highly social, as well as the conceptions of teaching and learning as processes of human activity mediated by human relations and of nature itself. An educative model oriented around the teacher s mediated activity in students zone of proximal development. The work intended to contribute to the advancement of pedagogical practices and in-depth academic discussion about the mediated activity and the zone of proximal development, as focuses of teachers performance, towards school teaching and learning problems.
Keywords: Teoria histórico-cultural; Materialismo histórico; Materialismo dialético; Ensino - aprendizagem; Análise microgenética; Dificuldade de aprendizagem; Educação Básica; Dificuldades de Ensino e Aprendizagem; Historical-Cultural Theory; Historical-Dialectical Materialism; Teaching; Learning; Microgenetic Analysis; Basic Education; Teaching and Learning Difficulties; CIENCIAS HUMANAS::EDUCACAO